Primer on disciplinary cases, for the use of deans and directors of U.P. Diliman and regional units. - University of the Philippines (Diliman). Office of the Vice-chancellor for Student Affairs. Student Disciplinary Tribunal (Quezon City The Tribunal, 1996)
Provides information for the dean and directors of the University of the Philippines Diliman and other regional units about the laws and the legal procedures of legal cases concerning students, faculties, and even non U.P. community members.
Keywords: University of the Philippines (Diliman) -- Handbooks, manuals, etc. -- Students; University of the Philippines (Diliman) -- Students -- Discipline; College discipline -- Philippines